Study the Effect of Poly Aromatic Hydrocharbons by Using Biochemical Tests in Chicken Embryos - Sarab,S.Kadhum; Sarab,R.Mustafa; Suha, A.Ali; Maha, M.taen; Melad.A Husien; Estabraq, N, Abdullateef (Institute of Medico-legal Publications Pvt Ltd, 2021)
The major risk of polycyclic aromatic hydrocarbons (PAHs) in all ecosystems originates from human raceactivity such as petroleum refining and other industrial processes. PAHs cause several effects at low dosesin animals in different ecosystem. The aim of this study was to assess the treatment of AL-Dura refinerywastes before being discharged to the river by studying their effects on the liver and renal functions inchicken embryos which used as a model exposed in vivo. One hundred and twenty local eggs were incubatedhorizontally at 37.5±0.5?C with a relative humidity of 65% in an egg incubator. Sixty eggs were used forhatchability study, were as other sixty eggs were used for biochemical analysis. On day 15th of incubation,the eggs were randomly divided into three different treatment groups and marked for identification. The firstA and second group B were exposed by injections with the residues of AL-Dura refinery (after treatment)and at the concentration of (2, 4) ppm respectively and 0.2 ml / egg into the air cell with sterile siring,then sealed with melted paraffin. Control group was injected with Olive oil. On day 18th of incubation thesamples of blood were collected from embryos. Liver function was measured using a biochemical assay withdiagnostic kits of specific enzymes (ALT, AST, and ALP). Ceratinine and urea level were measured to assesrenal function. The result showed a signenificant increase p? .05in the level of liver enzymes (ALT, AST),ceratinine and urea by increasing the exposure dose, were as there is a decrease in the level of ALP with theincreasing of exposure dose. Hatchability rat were significantly (p < 0.05) decreased with dose exposureincrease. Mortalities in the chicken embryos of all groups showed dose-dependent relationship. That showsthere are a clear effect of oil waste on liver and renal function, and an indication of the inefficient treatmentof these waste before being discharged to the river.